PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION UNTUK MENINGKATKAN KEMAMPUAN GERAK DASAR TARI ZAPIN SISWA KELAS V SD NEGERI 143 PEKANBARU - Yusro, Yuliska; Noviana, Eddy; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve basic motor skills Zapin dance in sdn 143 Pekanbaru by applyinglearning model Explicit Instruction for cultural arts lessons and skills. The subjects were students of class V SDN 143 Pekanbaru academic year 2016/2017 the number of students 23 people. This research is a classroom action research with two cycles. Each cycle has four stages, planning, action, observation and reflection. Instruments of data collection in this study is the observation sheet teacher, student observation sheet, rubric assessment process, and outcome assessment rubric. These results suggest that application oflearning model Explicit Instruction can improve basic motion dance Zapin fifth grade students of SDN 143 Pekanbaru. In preliminary data the average value of the basic motor skills Zapin dance student 43.69. In the first cycle the average value of 66.67 students and an increase of 52.60% from the initial data. Meanwhile, the second cycle of the average value of students increased to 85.44 and increased by 28.02 from the cycle I. This indicates that the application oflearning model Explicit Instruction can improve basic motion dance Zapin fifth grade students of SDN 143 Pekanbaru Key Words: learning Explicit Instruction model, zapin dance Capabilities